Expediente (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
In this issue, we present the Urdimento Editorial Team; editors, associate editors, thematic dossier editors, the editorial board, the body of evaluators working on this issue of Urdimento - We also present the editorial support team.
Keywords: expedient; editorial team; Urdimento